2007
DOI: 10.1007/s10661-007-9968-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of hydrobiological parameters of Narmada River water at Hoshangabad City, India

Abstract: Narmada is considered to be the lifeline of the state of Madhya Pradesh in Central India. The Narmada water is used for bathing, drinking, irrigation and industrial purposes. The city sewage and industrial effluent from Security paper mill at Hoshangabad drains in the Narmada River and pollutes the water quality. Urban sewage enters into Narmada through main nallas. River water quality at Hoshangabad has become a matter of concern due to continuous changing environment and increasing social and industrial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 6 publications
(5 reference statements)
4
16
0
Order By: Relevance
“…In addition, Seydisuyu stream was identified as class I‐II water quality in terms of pH and temperature. Sharma et al () found that temperature had negative correlation with DO ( r = –0.9), positive correlation with pH ( r = 0.96) and total coliform had positive correlation with temperature and pH and negative correlation with DO in Narmado River, India. Our data are in coherence with these findings in terms of correlation coefficient value amongst physical parameters (excluding total coliform and physical parameters).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Seydisuyu stream was identified as class I‐II water quality in terms of pH and temperature. Sharma et al () found that temperature had negative correlation with DO ( r = –0.9), positive correlation with pH ( r = 0.96) and total coliform had positive correlation with temperature and pH and negative correlation with DO in Narmado River, India. Our data are in coherence with these findings in terms of correlation coefficient value amongst physical parameters (excluding total coliform and physical parameters).…”
Section: Discussionmentioning
confidence: 99%
“…India is naturally gifted with holy rivers such as Ganga, Yamuna, Godawari, Cauvery, Narmada and many others, which are adorned with religious mythological tales, and worshiped in Indian culture [2,3]. Among these Indian rivers, Narmada is the 5 th largest west flowing peninsular river in central India and a lifeline for 1/4 th of the country's population [4]. Most townships and industrial complexes have been established around the banks of Indian rivers [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The results on the study will provide the preliminary information on the microbial load that may be useful in projecting the strategies required for the appropriate measures for remediation of the river water. A comparison on the pollution level of this river can be made with other rivers of India (Singh et al 2005a(Singh et al , b, 2007aSood et al 2008;Sharma et al 2008;Jonathan et al 2008) and other parts of the globe (Ayotamuno 1994;Djuikom et al 2006;Zheng et al 2008;Wang et al 2008;Moiseenko et al 2008;Chang 2008) which face the problem of contamination and pollution. Apart from these, a projection can be made regarding the possibility of enrichment in the downstream as a consequence of the pollutant levels.…”
Section: Introductionmentioning
confidence: 99%